Prevention of groundwater contamination from the pollutants released from dyeing industries using biochar produced from palm shell - Ravindiran G.; Jeyaraju R.M.; Nandipati G.; Seerangagounder S.; Al-Zaqri N.; Boshaala A.; Hayder G. (Elsevier B.V., 2024)
The dyeing process is regarded as a major source of water pollution. The availability of surface water is depleted as a result of these toxic contaminants. The wastewater produced by these dyeing processes enters fresh water and contaminates both surface and groundwater. Groundwater is regarded as a major source of water for domestic and agricultural use. The current study focused on removing toxic dye molecules from wastewater to protect groundwater. The performance of biochar, a palm shell product, was evaluated in terms of its ability to decolorize the Remazol Brilliant Blue R dye (RBBR). In this continuous process, the sorption mechanism is carried out by studying impact-creating factors such as flow rate (Lh?1), RBBR dye initial concentration (mg L?1), and sorbent depth (in cm). The present research investigated the maximum sorption capacity, which was found to be 46.61 mg g?1 at a sorbent bed height of 25 cm when combined with a solute flowrate of 0.3 L h?1 and an initial RBBR dye concentration of 100 mg L?1. The removal efficiency of the RBBR was obtained as 71.57%. The elutant for the regeneration studies was 0.01 M sodium hydroxide, and the results showed a 99.4% removal efficiency. 2023 Elsevier B.V.